Fostering Ki Hadjar Dewantara-Based Character Values Through Social Studies Learning Innovation For Primary School Students - Zulfiati, Heri Maria; Suyanto; Pamadhi , Hajar (International Journal of Psychosocial Rehabilitation, 2020)
This research aims (1) to describe Ki Hadjar Dewantara-based character values through the social sciences learning innovation, and (2) to identify character values within the social studies learning of Primary school students. The researchers used a qualitative approach; and the research data are elicited from the interview, observation and teachers’ documents. This research was conducted at Tamansiswa Primary School, Yogyakarta, Indonesia. This place was chosen as the research location because it applied educational concepts of Ki Hadjar Dewantara and the availability of information sources that could support researchers. While the research time frame occurred from November 2017 to January 2018. This research was conducted until the data obtained were saturated considerably. The result of research shows 1) Ki Hadjar Dewantara-based character values through the social sciences learning innovation for Primary school students comprising among system, the right to use the greeting of “salam dan bahagia”, the trilogy of leadership style, three NGAs and three centers of education, and 2) the character values imbedded within the social studies learning pertaining to Religiosity, discipline, Honesty, creativity and innovation, logical reason, social and environmental caring, curiosity, independence, nationalism, friendly, Responbility